Conveying interpretations of the past with interactive narratives - Harzem, Lars (My University, 2019)
This master’s thesis sketches a theory upon which a heuristic for the effective conveyance of scholarly historical interpretation of the past to a non-scholarly audience can be built. For this heuristic to yield methods that do not only respect academic standards of critical inquiry, but simultaneously ensure that thus produced historical knowledge can be imparted to and retained by laymen, the interplay of a range of factors has to be understood first. This thesis builds on and connects theories and concepts from philosophy, psychology, media- and game studies, cognitive sciences, semiotics, and computer science. It takes a stance that emphasizes the capacity of scholars and laymen alike to form informed and critical interpretations of the past under the right circumstances. In order to facilitate these circumstances most effectively, it takes a pragmatic approach which rejects maximizing either of the variables in the triplet verisimilitude, veracity, and verifiability at the expense of the other.
Keywords: history, education, interpretation, narrative, storytelling, media, interactive, games, digital